2010
DOI: 10.2220/biomedres.31.273
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alfacalcidol on muscle strength, muscle fatigue, and bone mineral density in normal and ovariectomized rats

Abstract: Vitamin D affects not only bone but also muscle to prevent falls and osteoporotic fractures. However, these effects on muscle and the mechanisms of fall prevention are still unclear. The purpose of this study was to investigate the effects of alfacalcidol [1α(OH)D 3 ] on muscle strength, muscle fatigue, and bone mineral density (BMD) in ovariectomized rats. Seven-month-old female Wistar rats were orally administered 1α(OH)D 3 or its vehicle everyday for 4 weeks after ovariectomy (OVX) or sham operation. Calf m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 49 publications
(44 reference statements)
2
15
0
Order By: Relevance
“…To the best of our knowledge, only two studies have examined this issue [16,17]. The first one, an animal study by Kasukawa et al [16], examined the effects of vitamin D supplementation on calf muscle fatigue in 12 ovariectomized rats.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only two studies have examined this issue [16,17]. The first one, an animal study by Kasukawa et al [16], examined the effects of vitamin D supplementation on calf muscle fatigue in 12 ovariectomized rats.…”
Section: Discussionmentioning
confidence: 99%
“…Several limitations in the present study warrant attention. First, the duration of treatment with alfacalcidol was only 4 weeks, although the length of treatment was determined based on previous studies (24). Duration of treatment appears to represent an important factor, and the effects of vitamin D treatment on muscles in glucocorticoid-treated animals should be further clarified in future studies by increasing the duration of administration.…”
Section: Discussionmentioning
confidence: 99%
“…At euthanasia, the right femur was harvested for BMD measurement. BMD at the proximal, middle, and distal thirds of the femur and total BMD of the femur were measured using dualenergy X-ray absorptiometry (QDR-4500 Delphi; Hologic, Bedford, MA, USA) (24). Protocols for all animal experiments were approved in advance by the Animal Research Committee of Akita University, and all subsequent animal experiments adhered to the "Guidelines for Animal Experimentation" of the university.…”
Section: Measurement Of Muscle Strength and Fatigabilitymentioning
confidence: 99%
“…In addition, all the patients received daily calcium (1,000-1,500 mg) and vitamin D (400-1,200 IU) during the study. Muscle strength, balance, and functional mobility depend on vitamin D serum levels [34,35]. Several previous studies have noted that treatment with vitamin D (alfacalcidol or calcitriol) can significantly reduce the risk of falls and of fall-associated fractures [34,36,37].…”
Section: Rycina 2 śRednie Liczby Punktów W Poszczególnych Domenach Kmentioning
confidence: 99%
“…Muscle strength, balance, and functional mobility depend on vitamin D serum levels [34,35]. Several previous studies have noted that treatment with vitamin D (alfacalcidol or calcitriol) can significantly reduce the risk of falls and of fall-associated fractures [34,36,37]. Hua Lin [23,38] reported that 5 mg zoledronic acid and calcitriol can significantly reduce the risk of falls in patients with postmenopausal osteoporosis.…”
Section: Rycina 2 śRednie Liczby Punktów W Poszczególnych Domenach Kmentioning
confidence: 99%